1960
DOI: 10.1017/s0021859600022425
|View full text |Cite
|
Sign up to set email alerts
|

The utilization of irrigated pastures by dairy cows II. The effect of stocking rate

Abstract: In an earlier experiment (Freer, 1959) it was found that the efficiency of year-round pasture utilization by dairy cows on irrigated pasture was no greater with a strip-grazing system (twice daily shifts) than with a rotational grazing technique (5-to 7-day shifts). The results of that experiment, in which both treatments were maintained at the same overall stocking rate, were discussed in relation to experiments of other workers in which differential stocking rates had been used. It became apparent during the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
6
0

Year Published

1963
1963
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 6 publications
2
6
0
Order By: Relevance
“…Continuously-stocked sheep increase grazing time to compensate for low rates of intake (Allden, 1962;Arnold, 1964). The grazing time of rotationally grazed cattle also tends to increase on short swards (Hancock, 1954;Freer, 1960), though Chacon and Stobbs (1976) found that the grazing time of their cows first increased, and then declined as Setaria swards were grazed down progressively over 10-14 d. The reduction in grazing time at low allowance in both experiments (Table 6) was therefore unexpected, though it is substantiated by recent evidence for strip-grazed dairy cows (Combellas and Hodgson, 1979;Le Du et al, 1979).…”
Section: The Influence Of Herbage Allowance On Grazing Behaviour and mentioning
confidence: 76%
“…Continuously-stocked sheep increase grazing time to compensate for low rates of intake (Allden, 1962;Arnold, 1964). The grazing time of rotationally grazed cattle also tends to increase on short swards (Hancock, 1954;Freer, 1960), though Chacon and Stobbs (1976) found that the grazing time of their cows first increased, and then declined as Setaria swards were grazed down progressively over 10-14 d. The reduction in grazing time at low allowance in both experiments (Table 6) was therefore unexpected, though it is substantiated by recent evidence for strip-grazed dairy cows (Combellas and Hodgson, 1979;Le Du et al, 1979).…”
Section: The Influence Of Herbage Allowance On Grazing Behaviour and mentioning
confidence: 76%
“…The main factor which can infiuence production per acre is stocking rate, but to achieve maximum production per acre, liveweight gain per animal is reduced. This has been demonstrated by many workers for both dairy and meat-producing animals (2,20,26,28,30,31,32,38,39). With dairy cattle, where the final product is milk, the intensity of stocking should be taken to the level where maximum production per acre is achieved, provided such treatment does not impair subsequent lactations, calf birth-weight and performance.…”
Section: Grazing Managementmentioning
confidence: 81%
“…In one of the earlier trials Holmes et al (1) found a 20-40% increase in production per acre from strip grazing in relation to paddock rotational grazing, when a 30% higher stocking rate was used in the former treatment. On the other hand McMeekan (9) and Freer (2) were unable to repeat this difference consistently when common treat-ment stocking rates were used. Lucas and McMeekan (8) and Line (7) have recently reported on experiments designed to diiferentiate between the contributions of stocking rate and grazing management to the differences obtainable from these two management systems.…”
Section: Introductionmentioning
confidence: 99%